The Matrix System at Work : An Evaluation of the World Bank's Organizational Effectiveness - Independent Evaluation Group (Washington, DC: World Bank, 2013)
The 1997 Bank reforms that introduced the matrix management concept aimed to adapt the organization to changing circumstances and address concerns among external stakeholders about the role of aid in development. The reforms were motivated largely by widespread recognition that the Bank's development programs were excessively driven by a culture of lending, with insufficient attention to client needs and the quality of results, which are crucial to development effectiveness. A previous round of reforms in 1987 had strengthened the country focus, but quality remained a concern. Furthermore, access of developing countries to development finance from the private sector had increased significantly, leading to a decreasing share of official development aid, including Bank financing, in total flows to developing countries. This trend has continued after slight interruption by the Asian financial crisis. In 1987, World Bank lending represented 15 percent of all external financing for developing countries. By 2002 Bank lending had declined to 4 percent of external financing (organizational effectiveness task force: final report, 2005). Changes in the external environment indicate that the matrix system is even more relevant today than when it was introduced. Client needs have diversified, with greater differentiation among countries, even within the regions; the growth of global public goods and corporate priorities is creating tensions and has given rise to new challenges which need to be reconciled with the country model; demand for cutting-edge knowledge is growing, both to enhance quality of lending and as a business line for policy and program advice to clients; and new global practices have emerged to meet needs such as information, communication and technology, and disaster management. The Bank's ability to renew itself and function as a truly global Bank is critical to its success.